2018
DOI: 10.3390/su10114152
|View full text |Cite
|
Sign up to set email alerts
|

Are Chinese Residents Willing to Recycle Express Packaging Waste? Evidence from a Bayesian Regularized Neural Network Model

Abstract: While enriching people’s lives, the rapid development of online shopping has posed a severe challenge to the environment. Questionnaires focusing on the intention to recycle packaging waste are designed. These questionnaires contain first-level variables such as recycling behavior attitude, recycling behavior cognition, situational factors, historical recycling behavior, and recycling behavior intention. With the collected questionnaire data, a regression analysis is first conducted on the selection of variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Wang et al [33] explored the positive effects of policy instruments, as external contexts, on attitudes and environmental behavior by analyzing the results of a questionnaire survey of 1145 residents in Shanghai. Integrating TPB and ABC theories, Feng and Hua [34] demonstrated that internal motivations and external contexts are essential variables in predicting recycling behavior.…”
Section: The Tpb-abc Integration Modelmentioning
confidence: 99%
“…Wang et al [33] explored the positive effects of policy instruments, as external contexts, on attitudes and environmental behavior by analyzing the results of a questionnaire survey of 1145 residents in Shanghai. Integrating TPB and ABC theories, Feng and Hua [34] demonstrated that internal motivations and external contexts are essential variables in predicting recycling behavior.…”
Section: The Tpb-abc Integration Modelmentioning
confidence: 99%
“…Further, Wan et al [ 28 ] collected survey responses from 198 Hong Kong residents, verifying that perceived policy effectiveness has a significant positive impact on behavioral intentions and contributes 19.39% to explaining recycling intentions. More recently, according to the calculation results of the Garson formula, perceived policy effectiveness as a situational factor has a higher sensitivity to intentions [ 31 ]. This study thus proposes the following hypotheses:…”
Section: Hypothesesmentioning
confidence: 99%
“…According to ABC theory, factors affecting behavior include attitude factors (e.g., norms, beliefs, values), situational factors (e.g., interpersonal influences, social expectations, advertising, government regulations, economic incentives, and costs), personal abilities (e.g., knowledge, specific actions, time allowance, money, social status, social–demographic variables), and habits or procedures [ 22 ]. A behavior occurs when the cumulative effect of external conditions and attitudes is positive [ 23 ]. Ertz, Karakas, and Sarigöllü [ 24 ] proposed that ABC theory’s attempt at perceived situational factors is a valuable exploration because it suggests that researchers examine subjectively perceived situational factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ertz, Karakas, and Sarigöllü [ 24 ] proposed that ABC theory’s attempt at perceived situational factors is a valuable exploration because it suggests that researchers examine subjectively perceived situational factors. Empirically, ABC theory has been applied in recent research on waste separation and recycling [ 23 ], consumer purchase behavior [ 25 ], and energy consumption [ 26 ]. Therefore, based on the ABC theory, this study added perceived policy effectiveness as an external environmental factor and knowledge as a personal ability factor.…”
Section: Literature Reviewmentioning
confidence: 99%